EXPOSURE NILAI TUKAR PADA PERUSAHAAN-PERUSAHAAN DI INDONESIA - Bahtiar Usman (Universitas Trisakti, 2003)
Measuring Exchange rate Exposure or elasticity between changes in firm value and ex- change rate measures is important for making decision in firm financing. Using 10 big firm in Indonesia from 1998 to 2003 monthly, we find that REE (Residual Elasticity Exposure) meth- ods is better than TEE (Total Elasticity Exposure), because inclusion of a market retum varlable has a dramaticinfluence in these model. So, we suggest for finance managers in Indonesia to use Exchange rate Exposure from REE Model.